ARABIC: اهتمام الإمام عبد الحميد الحاكمي بالقراءات في تفسيره المخطوط "تلخيص الدرر"دراسة نموذجية من سورة الأنعام إلى سورة طه: Imam Abdul Hameed al-Hakimi's interest in Al-Qira’at in his interpretation of the manuscript “Talkhis Ud-Durar” (An exemplary study from Surat Al-An'am to Surat Taha) - Nasurullah Qureshi (Rahat-ul-Quloob, 2022)
From the beginning of Islam to date, the scholars interpreted the Holy Qurʾān, all over the world. They performed their responsibilities of explaining the Holy Qurʾān according to the circumstances. As result of this, they left massive heritage in the field of Tafsir. However, a large number of these books could not be published and vanished with the pasage of time and huge number of these scholarly works is available in two forms; published and manuscript. Libraries of Turkey, Kingdom of Saudi Arabia, Berlin, Leiden and Sub-continent, are proud to have antique manuscripts. Tafsir Talkhis-ud-Durar of Allama Abdul Hameed Bin Abdul Majeed Al-Hakimi (514 A.H) is one of the notable manuscripts’ scholarship in the field of Tafsir. The manuscript is available in Noor-e-Usmania Library, Istanbul, Turkey, which is famous for the preservation of Islamic literature. The manuscript of Tafsir Talkhis-ud-Durar, exists in one volume of 425 sheets, each sheet contains two parallel pages. The language of the manuscript is Arabic, and scribe style is Arabic Naskh, while scribe used red color for Qurʾānic words and the black for the interpretation. This corpus of Tafsir is a valuable treasure of a well-learned and prolific brain of Allama Abdul Hameed Bin Abdul Majeed Al-Hakimi. He not only interprets the text of the Holy Qurʾān literally but also tries to relate the Qurʾānic message to the contemporary problems of his era, ranging from the life of individual to the broad spectrum of the collective sphere life. We may consider it among early interpretations of the Holy Qurʾān, which are far away from sectarianism and focus on message of the Holy Qurʾān and deal specifically with the social problems of the Muslims world.